Konflik Palestina-Israel Pada Masa Intifada II dalam Perspektif Konstruktivisme dan Strategi Politik - Sari, Amalia Tri Puspita (Indonesia Center for Middle East Studies, 2022)
Abstract The Palestinian-Israeli conflict has occurred since 1948 and continues to persist; until now, it has not ended. There were times when the conflict escalated, including in the period 2000-2005 known as the Intifada II. That period became a historic event in the 21st century, especially in the Middle East. Before the Second Intifada, there was the First Intifada (1987-1993) which became a symbol of the first physically planned resistance carried out by the Palestinian people after many attempts to resolve the conflict diplomatically. After the First Intifada, efforts were made to resolve the dispute through the Oslo Agreement. Still, Israel did not fulfill some of the promises made to the Palestinians, and the continued occupation and repression of the Palestinian people had triggered a more significant conflict until the Second Intifada (2000-2005) erupted. This article aims to map the variables involved in this conflict so that it is known which variables play a role in escalating and prolonging the conflict. The relationship between these variables is constructed based on systems thinking and visualized in a Causal Loop Diagram. Furthermore, the authors analyze this phenomenon with the perspective of constructivism and the concept of political strategy in conflict resolution. The finding of this study is that external actor, namely the United States, has taken the form of a Gradualism strategy through conflict manipulation so that the conflict becomes prolonged.